An Analysis of Mathematics-Integrated Scientific Literacy Competence of in-Service Teachers in Elementary School - Fitria, Yanti; Atikah, Nur (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
Living in the era of globalization, people are required to have literacy competencies in order to build and validate the knowledge received. Furthermore, rapid technological developments demand everyone to be better able to sort out opinions and facts, and to recognize biased content or fake news. Therefore, teachers, especially in-service teachers have an important role in improving literacy competence of elementary school students. They have to meet three scientific literacy competencies that are integrated in mathematics to improve their quality as educators. This study then aims to determine the integrated mathematical literacy competence of in-service teachers in elementary school. The competence consists of three indicators, including 1) being able to explain scientific phenomena, 2) being able to assess and apply scientific procedures, 3) and being able to interpret data. This descriptive study employs a test of ten questions as an instrument. The results of data analysis show that mathematics-integrated scientific literacy competence of in-service teachers in elementary school in explaining scientific phenomena, and assessing and applying scientific procedures is high. Meanwhile, integrated mathematics scientific literacy competence of the teachers in interpreting data is low.